PENGGUNAAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBASIS CANVA DALAM PEMBELAJARAN PKn DI MTsN 5 AGAM - Fitri Eliza; Buchari Nurdin; Azwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low interest and learning motivation of students in Civic Education (PKn) at MTsN 5 Agam, which has mostly relied on lecture methods with minimal use of technology. The objectives of this research are: (1) to design Civic Education learning using Canva-based animated video media, (2) to describe the implementation of this media in the learning process, and (3) to analyze the supporting and inhibiting factors in its use. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving Civic Education teachers and seventh-grade students. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the use of Canva-based animated video media creates a more engaging and enjoyable learning atmosphere and helps students better understand the material on religious diversity in Indonesia. Supporting factors include the availability of internet access, supporting devices such as laptops and projectors, and active student participation. However, challenges were found in limited facilities, particularly the number of projectors, classroom lighting, and video duration management that sometimes exceeded the allocated time. Overall, Canva-based animated video media is effective in increasing students’ interest and understanding in Civic Education learning. Keywords: Learning Media, Animated Video, Canva, Civic Education